Solving problems through technical and professional writing - Kennedy, George E. (McGraw-Hill, 1993)
Using a problem-solving approach, this book emphasizes the connection between writing and learning - learning to solve problems in and through technical communication. The text stresses the importance of the environment, which consists of such elements as the purpose of the document, the audience at which it is directed, the organizational culture in which it is produced and time constraints. Practical, real-world cases set the framework for each chapter, involving students in the processes of communication and problem analysis/solution. Contemporary technology communication theory is highlighted throughout and in addition, the book's emphasis on value and ethics should give students a balanced view of the connection between technology and humanities